Best practices in managing goal and strategies for multi-projects in building construction industry - Megat Abdullah, Aminatuzuhariah (Fakulti Alam Bina, 2009)
Managing a project is not similar to manage multi-projects. In one organisation, there might be several mix-types of projects that share resources. Many authors emphasise the importance of selecting the appropriate project mix for the portfolio. For example, CCTA (1994) states that candidate projects should meet one of these criteria, i.e.: projects should have shared objectives; projects should have shared resources that can be optimised by co-ordination across projects; and there should be strong interdependencies between projects having closely related technical interfaces and projects should be compatible with infrastructure plans. However, many problems are also being raised in managing such multiprojects. Some problems highlighted are such as: difficult to establish goal and strategies for multi-projects. This paper highlights some best practices that need to be considered in the preliminary stage of such projects. Some lessons learnt from the Commonwealth Games multi-project in Manchester shall also be discussed to reinforce the best practices